2011
DOI: 10.1007/s00784-011-0594-z
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of conventional and simplified resin-based luting cements to superficial and deep dentin

Abstract: This study evaluated the bond strengths of conventional (chemically and dual-polymerized) and simplified resin-based luting cements with their corresponding adhesives to superficial dentin (SD) and deep dentin (DD). Recently extracted third molars (N = 70, n = 10 per group) were obtained and prepared for testing procedures. After using their corresponding etchants, primers, and/or adhesive systems, the conventional and simplified cements (Variolink II [group A, conventional], Bifix QM [group B, conventional], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
1
33
0
2
Order By: Relevance
“…We thus only indirectly compared our results with other studies. Ozcan and Mese (2012) reported that simplified cements, such as Multilink Automix, showed inferior SBS to superficial and deep dentin compared with the conventional "etchand-rinse" adhesive systems, such as Variolink II and Panavia F2.0 10) . In this study, the adhesion systems were incrementally adhered onto the dentin surfaces using polyethylene molds (inner diameter 3.5 mm, height 5 mm), and only 500 thermocycles were performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus only indirectly compared our results with other studies. Ozcan and Mese (2012) reported that simplified cements, such as Multilink Automix, showed inferior SBS to superficial and deep dentin compared with the conventional "etchand-rinse" adhesive systems, such as Variolink II and Panavia F2.0 10) . In this study, the adhesion systems were incrementally adhered onto the dentin surfaces using polyethylene molds (inner diameter 3.5 mm, height 5 mm), and only 500 thermocycles were performed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current adhesive systems differ in their interaction with natural tooth structures 3,4) and various prosthodontic restorative materials 5,6) . Different factors can both predict and affect the adhesion and the bond strength: the luting cement composition 7,8) and microstructure of the curing adhesive layer 9) , the properties of the restoration material 1) , tooth surface 10) , the type of restoration 3) and a number of different factors observed throughout the working process, including pre-treatment 1,11,12) , treatment 3,[13][14][15][16] , and post-treatment 1,17) . During the pre-treatment phase of the cementation, it is important to clean the tooth surface because blood contamination of the dentin surface prior to bonding decreases the bond strength 11) ; however, dentin disinfection increases bond strength 12) .…”
Section: Introductionmentioning
confidence: 99%
“…Ayrıca RelyX U200'ün inisiyal pH'nın düşük olmasına rağmen dentin yüzeyinde belirgin bir demineralizasyon ve hibridizasyon meydana getiremediği için oluşturduğu hibrit tabakanın zayıf olması 40 düşük bağ dayanımını göstermesine neden olabilir. Yapısındaki demir ve 4-META/MMA güçlü bir adezyon sağlayan 41 SuperBond C&B rezin siman Özcan 30 'ın çalışmasıyla uyumlu olarak Variolink II ve Panavia F2.0 ile benzer, RelyX U200'den yüksek bağ dayanımı göstermiştir. Uzun dönemde adeziv bağda meydana gelen değişimleri inceleyen Hashimato 42 bağlanma ara yüzünde su miktarının zamanla arttığını ve bu suyun hibrit tabakadaki bozunmanın bir belirtisi olabileceğini bildirmiştir.…”
Section: Discussionunclassified
“…The substrate on which IDS was studied in this investigation was superficial dentin. It has been previously reported that superficial dentin is a favourable substrate for the "etch and rinse" system compared to the deep dentin [28].…”
Section: Discussionmentioning
confidence: 99%